Assessment of key interviewing factors for research assistants (AKIRA): development of a novel training and evaluation competency-based tool for mental health data collection in community settings - Cid-Vega, Alejandra; Best, Chynere; Pfeffer, Kendall; Sangraula, Manaswi; Wong, Janus; Gwaikolo, Wilfred; Caracoglia, James; Rai, Sauharda; Brown, Adam D.; Kohrt, Brandon (Frontiers in Education, 2025)
Data quality is critical in mental health research, yet there is considerable variability in the training and preparation of those involved in data collection. Individuals with limited research training often play a central role in collecting data and, to date, no systematic means of evaluating researcher competencies exists. The Assessment of Key Interviewing factors for Research Assistants (AKIRA), a competency-based tool for researchers conducting interview-based mental health data collection with communities, aims to address this gap. AKIRA provides a systematic framework for the training, monitoring and evaluation of data collectors, by identifying key interviewing behaviors across 10 domains, and assessing research assistants for mastery, areas for improvement, and displays of harmful behaviors in these domains. With an emphasis on cross-cultural interactions, the AKIRA is designed to be easily adapted to various implementation contexts. Given the information gaps in mental health research, and the importance of monitoring and evaluation in the development and guidance of mental health interventions, AKIRA may enhance data quality and research especially in community mental health settings where the experiences and training of individuals involved in research and data collections may vary considerably and would benefit from competency-based trainings to support this complex work.